Leverage Sebagai Pemoderasi Hubungan Good Corporate Governance, Pengungkapan Corporate Social Responsibility, dan Agresivitas Pajak Terhadap Financial Distress Perusahaan Pertambangan yang Terdaftar pada Daftar Efek Syariah Indonesia - Jamilah, Isnawati; Sujianto , Agus Eko; Asiyah, Binti Nur (Masyarakat Ekonomi Syariah Bogor, 2025)
Financial statements serve as a communication tool between companies and stakeholders, providing signals about financial conditions, policies, and other relevant information to support decision-making activity. In practice, financial statements often fail to adequately convey the risk of corporate bankruptcy. Stakeholders must remain vigilant to various conditions that may affect a company’s financial health and lead to financial distress. This study aims to analyze the influence of Good Corporate Governance practices, Corporate Social Responsibility disclosure, and tax aggressiveness on the financial distress of mining companies listed in Indonesia’s Sharia Securities List, with leverage as a moderating variable. Employing a quantitative approach and secondary data from 144 semiannual financial reports, the study applies multiple linear regression and moderation analysis. The results reveal that all three independent variables significantly affect financial distress when tested simultaneously. Partially, Good Corporate Governance and tax aggressiveness show significant effects, while Corporate Social Responsibility does not. Leverage is found to moderate the relationship between each independent variable and financial distress, highlighting the critical role of debt levels in amplifying or mitigating the impact of governance, CSR, and tax strategies on a company’s financial condition.